American pastoral - Roth, Philip (Houghton Mifflin, 1997)
The tragic impact of the Vietnam War on a relationship between father and daughter. The father is an upstanding individual who believes in the American Dream, but his daughter has a different dream, to get America out of Vietnam and she kills innocent people to achieve it. For the father it is the end of the world, he has lost his daughter.